La mobilisation des morts : culte du souvenir et culture de guerre en France pendant la Grande Guerre - Christina Theodosiou (Revue LISA)
As early as August 1914, commemorative action honoring the dead served to sustain the war effort and encourage national mobilization. Based on a system of values celebrating sacrificial heroism, commemoration aimed at justifying the conflict and at giving sense to violent death on the battlefield. During the Great War, commemorative homage gave rise to a symbolic narration about the past, the present and the future which was seeking to conceptualize collective mourning and mobilize civilians in favor of the pursuit of the war until final victory.